Electromechanical Microinjection of Pink Bollworm Pectinophora gossypiella Embryos Increases Survival. (March 1997) - Peloquin, John J.; Thibault, Stephen T.; Schouest, Leo P.; Miller, Thomas A.
We report and compare methods and apparatus for injection of pink bollworm, Pectinophora gossypiella (Saunders), embryos. Injection with an electromechanical device resulted in 59% survival of embryos. Previous techniques relying on a mechanical manipulator resulted in 8% survival. Pink bollworm (PBW) embryo injection technology is based in part on methods developed for injection and genetic transformation of Caenorhabditis elegans ([Maupas] Dougherty) and Drosophila melanogaster (Meigen) with substantial alterations in both method and apparatus to accommodate special conditions of PBW biology, behavior and morphology. The microinjection methodology described here has direct application to other difficult-to-inject insects and invertebrates.